Analisis Modal Usaha, Kualitas Produk, Jaringan Wirausaha Terhadap Keberlanjutan Usaha UMKM Wilayah Pesisir Madura - Hadyarti, Vidi; Setyo Dwi Purnomo, Arie (Bahtera Inovasi, 2023)
Micro, Small and Medium Enterprises (MSMEs) are a group of businesses that have a large percentage of contribution in Indonesia. Madura is one of the regions in East Java Province whose economy is supported by the MSME sector. In the micro economy, the existence of MSMEs is very fluctuating, this can occur due to a shift in the business sector to follow the existing market share because they have unestablished capital. In the macro economy, the development of MSMEs always shows an increasing percentage, so that business continuity needs to be maintained. MSMEs in Madura must be able to face the challenges that are increasingly rapidly marked by the many offers of similar products in various sales distribution channels. The number and development of traditional retail, modern retail, social media and marketplaces, makes MSMEs in Madura need to maintain their business continuity so that they can survive and develop by improving factors that are a major influence on micro, small and medium enterprises. The factors in question such as in terms of increasing business capital, in terms of product quality and quality and in terms of entrepreneurial networks. This study aims to determine what factors must be considered for the sustainability of MSMEs in Madura. So that MSME actors can compete and maintain their businesses in today's increasingly rapid challenges. Business capital is often synonymous with money, but capital can be in the form of machinery, vehicles, buildings, raw materials, and many others to run business operations. Quality and product quality are very strategic approaches in maintaining business continuity, so MSMEs in Madura must have good quality standards and product quality. This entrepreneurial network is a collaboration with other business units that can strengthen the business position in the market.